The Impact Of Entrepreneurship On Economic Growth In Industrialized Countries Covering 2001-2019 - Mekhzoumi, Lotfi; Gharbi, Hichem (جامعة الوادي University of Eloued, 2021)
This paper aims to examine the impact of entrepreneurship on economic growth, using GDP per person employed as dependent variable, and entrepreneurship computed by Total Early-Stage Entrepreneurial Activity (TEA), Financing for Entrepreneurs (FNCENT), and Government Entrepreneurship Programs (GEP) as independent variables; and other control variables. The data consists of 28 industrialized countriescovering 2001–2019. The estimation results of an augmented Solow panel data model of 28 industrialized countries covering 2001–2019, reached to a significantly negative impact only of (TEA) in the in static model. While the dynamic panel GMM estimation indicates a significantly negative impact of (TEA), and a significantly positive impact of (GEP).
مقال
Keywords: Entrepreneurship, Economic Growth, Fixed-Effects, System-GMM